Efektifitas Prenatal Yoga Dalam Mengatasi Nyeri Persalinan - Nur Zuwariyah; Uliyatul Laili (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Mothers giving birth will feel pain in the opening phase and decrease due to uterine contractions. Pain management can be processed since pregnancy with prenatal yoga. The purpose of this study was to determine the effectiveness of prenatal yoga on labor pain that occurs in the first stage. This study was conducted using a quasi-experimental method. Sampling was carried out from April to June 2020. The research sample was 40 people, which were taken using the consecutive sampling method. Inclusion criteria in this study were pregnant women with gestational age 30 weeks with physiological pregnancy. Furthermore, data analysis was carried out by comparing the group that did prenatal yoga and the group that did not do prenatal yoga. Data analysis was carried out univariately with frequency distribution and bivariate with Mann Whitney test. The results showed that the average pain scale felt in the prenatal yoga group was 5.8 while the group that did not do prenatal yoga was 8.1. Statistical analysis showed a p value of 0.001 < 0.005, which means that there is a difference in pain scale between the prenatal yoga group and not. It can be concluded that the implementation of prenatal yoga is effective in overcoming labor pain